Analisis Implementasi Pengelolaan Keuangan Badan Layanan Umum Rumah Sakit Umum RSUP Dr. Wahidin Sudirohsodo Makassar - Qaiman, Bahar; Muspa, Muspa; Arman, Agus (Patria Artha Management Journal, 2018)
ABSTRACT This Analysis of Financial Management Implementation of Public Service Agency ofRSUP Dr. General Hospital. Wahidin Sudirohusodo Makassar. The purpose of this studywas to find out about the implementation of financial management of the Central PublicService Agency that has been implemented by the General Hospital Center Dr. WahidinSudirohusodo Makassar and its impact on the performance of hospital services. Thisresearch uses descriptive approach. The method of analysis to be used by the authors inthis study is the method of quantitative analysis that is using the analysis of FinancialRatios based on Regulation of the Director General of Treasury Number: Per-34 / PB /2014. The results of the analysis show the financial condition of Dr. WahidinSudirohusodo Makassar during the year 2013-2016 is quite good, based on Regulation ofDirector General of Treasury Number: PER-34 / PB / 2014. Dr. Wahidin SudirohusodoMakassar, which has an overall financial ratios and revenues of BLU, is 79% with arating of financial performance classified as "healthy enough"